Psychological and Pedagogical Foundations of the Formation of Students' Own Educational Strategies in the Process of Independent Learning - Tsyganova, Larisa V. (2020)
The scientific problem to which this article is devoted is determined by the tasks facing modern education. One of these tasks is to build a continuous education system, covering all stages of a person’s life. To ensure the movement of the individual in the educational space, it is necessary to form a culture of lifelong learning, which implies the development of technologies of self-education and self-learning. The latter become a fundamental factor in the system of continuous learning. The analysis of pedagogical, psychological and methodical literature showed that the independent work of students in its theoretical justification has always been interpreted as the most important component of the educational process. However, in recent years the problem of improving its effectiveness began to attract increasing attention of researchers. One of the ways, according to scientists, psychologists and methodologists, is to teach students the ability to learn. But in order to "learn how to learn", it is necessary to master various methods of organization and implementation of educational activities. This is facilitated, according to foreign scientists, by the use of various learning strategies. The purpose of this article is to consider different types of educational strategies formed within the framework of independent foreign language training of students. According to the authors of the article, educational process should be organized in such a way that the consistent and purposeful work on formation of teaching strategies is conducted, mastery of which promotes students’ ability to learn. The formation of this skill becomes a support for personal readiness to continuously learn throughout life.